Inglés Intermedio 2 - Montiel Lira, Diana Alicia (My University, 2002)
INDICE 1.- CAPITULO UNO. 1.1 Sickness symptoms and remedies. 1.2 Simple past verb to be affirmative form. 1.3 Simple past verb to be negative form. 1.4 Simple past verb to be interrogative form. 2.- CAPITULO DOS. 2.1 Simple past regular verbs. 2.2 Simple past irregular verbs. 2.3 Simple past interrogative form. 2.4 Simple past negative form. 3.- CAPITULO TRES. 3.1 Conversation. 3.2 Idiomatic future. 3.3 Idiomatic future negative form. 3.4 Idiomatic future interrogative form. 3.5 Vocabulary.
Keywords: Inglés intermedio 2; Sickness, symptoms, remedies, past tense, simple present, simple past, idiomatic future, going to, present, past, past negative